How and to what extent did private actors influence Basel III? - Jannike Gottschalk Ballo (Freie Universität Berlin, Center for International Political Economy, 2012)
This paper deals with the actors and the changing power relations involved in global financial regulation. It explores the private sector's influence on Basel III regulatory reforms, which were formulated by the Basel Committee on Banking Supervision as a response to the global financial crisis following the US subprime mortgage crisis in 2007-2008. Scholars argue that the dynamic between market actors and regulators of international finance has experienced a shift in power during the last couple of decades. Banks and other financial institutions have become more influential at the expense of states and regulatory institutions. This essay argues that private actors are important to ensure legitimacy and efficiency of regulation, and finds that they possess far greater powers than their consultative positions towards regulators might indicate.
Keywords: 330